Steroidal Adducts and Andrastin-Type Meroterpenoids from the Co-culture of Two Isodon Species-Associated Endophytic Fungi - Zhang, Qiao-Peng; Hu, Kun; Tang, Jian-Wei; Su, Xiao-Zheng; Li, Xiao-Nian; Sun, Han-Dong; Puno, Pema-Tenzin (Synlett, 2025)
Ergopolyketides A–D, presumably biosynthesized through Diels–Alder additions between ergosterol and polyketides, along with two new andrastin-type meroterpenoids, isopenicins D and E, were isolated from the co-culture of endophytic fungi Penicillium sp. sh18 and Pestalotiopsis sp. HS30, both, inhabiting Isodon species. The structures of these compounds were elucidated using spectroscopic analysis, single-crystal X-ray diffraction, and quantum chemical calculations. Isopenicin D and a known compound, peniandrastin D, exhibited moderate cytotoxic activities against human cancer cell lines HL-60, A549, and SMMC-7721, with IC50 values ranging from 13.37 to 29.17 μM.
Keywords: Isodon; endophytic fungi; steroidal adducts; andrastin-type meroterpenoids; cytotoxic activity; quantum chemical calculations; configuration determination